If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3x-4)=2x-8+4x
We move all terms to the left:
2(3x-4)-(2x-8+4x)=0
We add all the numbers together, and all the variables
2(3x-4)-(6x-8)=0
We multiply parentheses
6x-(6x-8)-8=0
We get rid of parentheses
6x-6x+8-8=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| x-30+4x=70 | | 9=z-11 | | 8/3-4x=5/2x+¼ | | 5(2x-1)+7x=2(x-8) | | y=1.2^5+3.5 | | 11(2x–3)=5(2x+2)+5 | | c-(-5=14) | | 6+9x=456 | | x+2x+13=106 | | -31=20x-15-12x | | X+9/12=-2x-½/3 | | X=1129-x | | 14-7w+3w+12=122 | | -10x+5+3x=12 | | 3g/4=-12 | | 8(4+x)=46 | | −9b+2=83 | | 3x-7x+8=11 | | 120+130=250x= | | 1228+2x=5(x−2) | | y=18=25 | | P^2+16p-64=0 | | w-3=23 | | 14x+22=-13x+5 | | 8x-(6-2x)=2(5x+3) | | 7x^2+11-6=0 | | -4x+4+x=-5 | | 3(h+5)=-5 | | 4x+26+2x=140 | | 13=k-9 | | 2x31=4x | | 1/3(9x-15)-4(4x-3)=1/2(4x-8)-3/4(12x-8) |